Randomized, Double-Blind, Placebo-Controlled, Global Phase III Trial of Talimogene Laherparepvec Combined With Pembrolizumab for Advanced Melanoma. Issue 3 (23rd August 2022) - Chesney, Jason A.; Ribas, Antoni; Long, Georgina V.; Kirkwood, John M.; Dummer, Reinhard; Puzanov, Igor; Hoeller, Christoph; Gajewski, Thomas F.; Gutzmer, Ralf; Rutkowski, Piotr; Demidov, Lev; Arenberger, Petr; et al.
Abstract : PURPOSE: The combination of talimogene laherparepvec (T-VEC) and pembrolizumab previously demonstrated an acceptable safety profile and an encouraging complete response rate (CRR) in patients with advanced melanoma in a phase Ib study. We report the efficacy and safety from a phase III, randomized, double-blind, multicenter, international study of T-VEC plus pembrolizumab (T-VEC-pembrolizumab) versus placebo plus pembrolizumab (placebo-pembrolizumab) in patients with advanced melanoma. METHODS: Patients with stage IIIB-IVM1c unresectable melanoma, naïve to antiprogrammed cell death protein-1, were randomly assigned 1:1 to T-VEC-pembrolizumab or placebo-pembrolizumab. T-VEC was administered at ≤ 4 × 10 6 plaque-forming unit (PFU) followed by ≤ 4 × 10 8 PFU 3 weeks later and once every 2 weeks until dose 5 and once every 3 weeks thereafter. Pembrolizumab was administered intravenously 200 mg once every 3 weeks. The dual primary end points were progression-free survival (PFS) per modified RECIST 1.1 by blinded independent central review and overall survival (OS). Secondary end points included objective response rate per mRECIST, CRR, and safety. Here, we report the primary analysis for PFS, the second preplanned interim analysis for OS, and the final analysis. RESULTS: Overall, 692 patients were randomly assigned (346 T-VEC-pembrolizumab and 346 placebo-pembrolizumab). T-VEC-pembrolizumab did not significantly improve PFS (hazard ratio, 0.86; 95% CI, 0.71 to 1.04; P = .13) or OS (hazard ratio, 0.96; 95% CI, 0.76 to 1.22; P = .74) compared with placebo-pembrolizumab. The objective response rate was 48.6% for T-VEC-pembrolizumab (CRR 17.9%) and 41.3% for placebo-pembrolizumab (CRR 11.6%); the durable response rate was 42.2% and 34.1% for the arms, respectively. Grade ≥ 3 treatment-related adverse events occurred in 20.7% of patients in the T-VEC-pembrolizumab arm and in 19.5% of patients in the placebo-pembrolizumab arm. CONCLUSION: T-VEC-pembrolizumab did not significantly improve PFS or OS compared with placebo-pembrolizumab. Safety results of the T-VEC-pembrolizumab combination were consistent with the safety profiles of each agent alone.